Anatomical bases and initial clinical application of the intrahepatic Glissonian approach in hepatectomies. - Castro, Álvaro; Murias, Federico; Cerchiari, Emilia; Curi, Jorge; González, Fernando; Olivera, Eduardo; Machado, Marcel Autran (Cirugía del Uruguay, 2022)
Introduction: Pedicle control during liver resections can be done by extrahepatic hilar dissection (EHD) or the Glissonian approach (GA). Intrahepatic GA (IGA) according to the Machado technique can offer certain advantages, especially in difficult dissections. However, it is used less than the DHE. Objective: to analyze the anatomical bases of the IGA and to communicate our initial clinical experience. Material and methods: IGA according to the Machado technique was performed on six (6) cadaveric livers. Liver dissection was then performed to assess the effectiveness of pedicle loading and measure the depth of the different Glissonian pedicles. The clinical application of the technique was gradual and selective, applying it when it seemed feasible and that it provided some advantage over DUS. Results: in the 6 cadaveric livers it was possible to load all the Glissonian pedicles (lobar and sectoral bilaterally, as well as the left segmental ones). These are found at a depth of less than 2 cm from the hepatic capsule, being accessible for control by IGA. The main exception is the right anterior pedicle, whose origin is deeper, which, associated with its cephalad and sometimes branched origin, can make it more difficult to load. The application of the IGA was carried out in 5 patients, in all of them it was effective, it took little time and there were no intraoperative complications. Conclusions: the IGA according to the Machado technique is a systematic, reproducible, feasible and safe procedure, even in its initial clinical application. The anatomical knowledge of the Glissonian pedicles is essential to carry it out successfully